The Influence of Culture, Personal Growth, Price, and Attractions on Ecotourism Satisfaction and Revisit Intention to Grafika Cikole Tourism Terminal (TWGC) - Nirmala Eka Chandra; Megawati Simanjuntak; Istiqlaliyah Muflikhati (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2025)
This study investigates the impact of cultural elements, personal development, pricing strategies, and tourist attractions on visitor satisfaction and their intent to revisit the Grafika Cikole Tourism Terminal (TWGC) in West Java, Indonesia. The central research problem addressed is the fluctuating number of tourists at TWGC in recent years, potentially threatening the site's sustainability as an ecotourism destination. This fluctuation prompts the need to understand the underlying factors that influence tourist satisfaction and revisit intentions. Utilizing a sample of 210 respondents, data were analyzed through Structural Equation Modeling (SEM) to elucidate the relationships among the identified variables. The findings indicate that pricing emerged as the most significant determinant of customer satisfaction and tourists' propensity to return to TWGC. Additionally, cultural engagement was found to play a pivotal role in enhancing visitor experiences. Based on these insights, several managerial implications are proposed to bolster tourist interest and satisfaction. These include the enhancement of cultural events, diversification of traditional culinary offerings, the organization of regularly scheduled performances aimed at senior visitors, the introduction of innovative events, and the establishment of competitively priced tour packages. This research contributes to the understanding of the critical factors influencing tourist satisfaction and retention in Indonesian tourism, providing actionable recommendations for stakeholders in the industry.